The four-and-a-half-LIM-domain Protein FHL2 is a novel regulator of pulmonary fibrosis - Banthien, Nils; Justus Liebig University Giessen (My University, 2018)
Idiopathic pulmonary fibrosis (IPF) is a progressive and grave lung disease and its etiology is insufficiently understood. Defects in TGF-beta signaling and WNT signaling are deemed to be of major relevance to the pathogenetic process of IPF. The LIM protein FHL2 has been shown to modulate TGF-beta signaling and WNT signaling in various cellular contexts. It may also serve as an interface for crosstalk between the two pathways. FHL2 is known to regulate fibrogenesis and to promote fibroblast to myofibroblast transition and epithelial-to-mesenchymal transition (EMT), which are deemed to constitute key events in IPF. FHL2 is often characterized as profibrotic in nature. Nevertheless, it has also been ascribed antifibrotic properties in the bleomycin-mouse-model of IPF. To date, nothing is known about a possible involvement of FHL2 in human IPF.This study examines the expression, localization and function of FHL2 in IPF. Quantitative (q)RT-PCR performed on lung homogenates displayed a 3.25-fold upregulation of FHL2 mRNA levels in IPF lungs compared with controls (transplant donors). Western blot analysis of the same material confirmed a significant upregulation of FHL2 protein in IPF lungs. Using immunohistochemistry, FHL2 was localized to fibroblasts, as well as to bronchial and alveolar epithelial cells in IPF lungs and in healthy lungs. Stimulation of human fibroblasts with TGF-beta resulted in enhanced expression of FHL2 mRNA (3.2 fold) and protein (4.2 fold). Finally, overexpression of FHL2, led to a significant potentiation of Smaddependent TGF-beta signaling in NIH-cells, as assessed by Luciferase assays and phospho Western blots. In conclusion, these results suggest that FHL2 might act as a profibrotic regulator in IPF.

Die idiopathische pulmonale Fibrose (IPF) ist ein chronisch-fortschreitendes und schweres Lungenleiden von nur unzureichend geklärter Ätiologie. Defekte in den TGF-beta- und WNT-Signalwegen scheinen eine zentrale Bedeutung in der Pathogenese von IPF zu haben. Das LIM Protein FHL2 moduliert bekanntermaßen den TGF-beta- als auch den WNTSignalweg in verschiedenen zellulären Kontexten. Kontextspezifisch vermittelt es auch Crosstalk zwischen beiden Signalwegen. Neben der Möglichkeit zur Regulierung verschiedener fibrose-bezogener Prozesse, verfügt FHL2 über die Kapazität, die Transition von Fibroblasten zu Myofibroblasten und die epithelial-mesenchymale Transition (EMT) zu fördern, welche beide als zentrale Prozesse in der Entstehung von IPF gelten. Dem Molekül wird generell ein profibrotischer Charakter zugeschrieben. Es zeigt jedoch auch antifibrotische Eigenschaften im Bleomycin-Maus-Modell der IPF. Bis dato ist nichts über eine Beteiligung von FHL2 an der Entstehung und Aufrechterhaltung der humanen IPF bekannt. Diese Studie untersuchte die Expression, Lokalisation und Funktion von FHL2 in IPF. An Lungenhomogenat durchgeführte quantitative (q)RT-PCR-Untersuchungen zeigten eine 3,25-fach verstärkte Expression von FHL2-mRNA in IPF-Lungen im Vergleich zu gesunden Spenderlungen. Western Blots des gleichen Materials bestätigten eine signifikante Hochregulation von FHL2-protein in IPF-Lungen. Immunhistochemische Untersuchungen lokalisierten FHL2 in Fibroblasten als auch in bronchialen und alveolären Epithelzellen von IPF-Lungen und gesunden Spenderlungen. Die Stimulation humaner Fibroblasten mit TGF-beta resultierte in einer verstärkten Expression von FHL2-mRNA (3,2-fach) und FHL2-Protein (4,2-fach). Schließlich zeigte sich in Luziferase-Assays und phospho-Western Blots, dass die stabile Überexpression von FHL2 in NIH-Zellen eine signifikante Potenzierung des Smad-abhängigen TGF-beta Signalweges bewirkt. Zusammenfassend suggerieren diese Ergebnisse profibrotische Eigenschaften von FHL2 in IPF.
Keywords: ddc:610